Anxiety and Depression among Patients Admitted at COVID wards of East Avenue Medical Center (EAMC) Using the Validated Filipino Version of the Hospital Anxiety and Depression Scale (HADS-P) - F.J. Guiang; M.A. Gabaon (European Psychiatry, 2022)
Introduction